Plant-parasitic nematode disease complexes as overlooked challenges to crop production - Parrado, Luisa M.; Quintanilla, Marisol (Frontiers in Plant Science, 2024)
Plant diseases are caused by various microorganisms such as bacteria, fungi, viruses, and nematodes. These diseases impact crop growth, reduce produce quality, and lead to financial losses. Plant disease can be caused by single pathogens or by interactions called "disease complexes", involving two or more pathogens. In these cases, the disease severity caused by the pathogens combined is greater than the sum of the disease caused by each pathogen alone.Diseases complexes formed among plant-parasitic nematodes (PPNs) with bacteria, fungi, or viruses, can occur. PPNs either enhance the other pathogen incidence and severity or are necessary for disease symptoms to be expressed. PPNs can do so by being wounding agents, vectors, modifiers of plant biochemistry and physiology, or altering the rhizosphere microbiome. This review identifies several PPNs-plant pathogens disease complexes in crop production to discuss how understanding such interactions is key for improving management practices.